1984
DOI: 10.3171/jns.1984.60.4.0845
|View full text |Cite
|
Sign up to set email alerts
|

Dysplastic gangliocytoma of cerebellum in a newborn

Abstract: Dysplastic gangliocytoma of the cerebellum is reported in a newborn. It is characterized by large ganglion cells in the molecular layer and premature attenuation of the external granule-cell layer. The internal granule-cell layer appears rarefied but otherwise normally organized. It appears that in this disease the migrating granule cells mature too early and become arrested in the molecular layer, because of their abnormal forms, while others continue to migrate and grow in size in their normal location in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

1985
1985
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(12 citation statements)
references
References 10 publications
0
10
0
2
Order By: Relevance
“…Cases have been described at all ages, from newborns [6,25] to elderly patients, although the adult cases predominate. The form of presentation is quite unspecific, usually consisting of hydrocephalus and macrocephaly in children, and in longstanding gait disturbance and ataxia later on complicated by intracranial hypertension due to the acquired large volume of the lesion in the adult Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Cases have been described at all ages, from newborns [6,25] to elderly patients, although the adult cases predominate. The form of presentation is quite unspecific, usually consisting of hydrocephalus and macrocephaly in children, and in longstanding gait disturbance and ataxia later on complicated by intracranial hypertension due to the acquired large volume of the lesion in the adult Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The authors divided the patients into two groups; those with a MIB-1 LI of <2%, and those with a MIB-1 LI of >2%. There is no gender or racial predilection (Roessmann & Wongmongkolrit 1984;Faillot et al 1990), unless LDD is found in association with Cowden disease in which case there is a 1 : 4 male:female preponderance (Murata et al 1999). Recently, Lenzi et al (2006) published an algorithm for treatment of CNs, based on an experience of 20 patients with CNs.…”
Section: Clinical Outcomementioning
confidence: 99%
“…The authors originally described the lesion under the name of “ganglioneurome myélinique diffus de l'écore cérébelleuse”. Subsequently, this entity was referred to by a variety of synonymous descriptions, such as diffuse ganglioneuroma of the cerebellar cortex (2, 3) (benign) hypertrophy of the cerebellum (4–6), Purkinjoma (7), hamartoma of the cerebellum (2, 8), gangliocytoma myelinicum diffusum of the cerebellar cortex (9), dysplastic gangliocytoma of the cerebellum (10–14), granule cell hypertrophy of the cerebellum (15) or simply Lhermitte–Duclos disease (16–20).…”
mentioning
confidence: 99%